Socio-Economic Aspects of Home Trade Internationalization - Oripova Gulirano Nodirovna (Peerian Journals Publishing, 2023)
The issues of internationalization of internal trade of Uzbekistan are considered. The socio-economic aspects and consequences of this process are revealed. There are two trends of internationalization of the trade sector of Uzbekistan: the expansion of imports and the large-scale penetration of foreign trade capital into the sphere of commodity circulation. The attention is focused on the strategic mistakes of trade policy in the field of wholesale trade, which led to blocking the entry of domestic producers into the market and stimulating commodity imports. It is proved that the expansion of imports of goods to Uzbekistan has essentially blocked the weakly competitive domestic commodity production. The share of domestic goods in turnover has reached a critically low level in comparison with the standards of national economic security. It is indicated that domestic and foreign investments have different directions. Domestic investment funds are directed mainly to the development of trade in cars and other vehicles, as well as retail trade. Foreign investments, on the contrary, reveal the growing interests of foreign investors in wholesale trade - a sector that is currently backward and important in the future. The factors that determine the investment attractiveness of the domestic consumer market of Uzbekistan are given. The relevance of the study is explained by the globalization of commodity markets and the little-studied theoretical and applied aspects of internationalization
Keywords: domestic trade; globalization; internationalization